Factors affecting the visual outcome of pediatric cataract surgery: a hospital based prospective study in eastern Nepal - Chaudhary, Santosh; Lavaju, Poonam; Shrestha, Bhuwan Govinda; Shah, Sangeeta; Chaudhary, Sanjib Kumar (Nepalese Journal of Ophthalmology, 2018)
The World Health Organization’s (WHO) global initiative for the elimination of avoidable blindness by the year 2020 (Thylefors et al., 1995) has prioritized the control of childhood blindness. Currently cataract remains one of the most important causes of treatable blindness in children (Giles et al., 2016). In Nepal, as in other developing countries, cataract is believed to be a leading cause of blindness in children. According to The Nepal Blindness Survey from 1978 to 1980, congenital cataract accounted for 16.3% of blindness detected in children under the age of 15 years (Brilliant et al., 1985). Epidemiology of Blindness in Nepal 2012 survey has suggested that the prevalence of childhood blindness has reduced from 0.68% in 1981 to 0.4% in 2011 (Sapkota, 2012).